PELESTARIAN TRADISI LOKAL DALAM UPAYA MEWUJUDKAN HARMONI (Studi Pada Masyarakat Nagari Koto Baru, Kecamatan Luhak Nan Duo, Kabupaten Pasaman Barat) - Syafnal, Syafnal; Jendrius, Jendrius; Elfitra, Elfitra (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The diversity of religions found in the New Koto Nagari does not lead to inter-religious conflict. This is because the local people preserve local traditions that are derived from the habits of their elders. Harmonious relations between religious communities are created through the practices of local traditions of village consultation, village clean, celebration of as-syuro day, kenduri and commemoration of August 17. Local tradition serves as a special mechanism that can prevent the community from possible conflicts between religious communities and is able to clean up the chaotic community atmosphere. Local traditions contribute to resolving several inter-religious conflicts, such as: Conflict of establishment of Kosta Beach church and widening of the terrace of the Mahakaraya Holy Family church, conflict of pig breeding in Jorong and Jakarya Mahakarya, and conflict in organizing blood donor activities in the Holy Family Mahakarya church.